PENGETAHUAN GIZI DAN KEJADIAN SINDROM METABOLIK PADA LANSIA DI KELURAHAN JOMBLANG KOTA SEMARANG - Candra, Aryu (Universitas Diponegoro, 2019)
BackgorundThe high incidence of malnutrition in the Jomblang village is partly due to a lack of knowledge about healthy food. Elderly has the ability to receive knowledge and skills about nutrition so that they can be directly targeted for programs to increase knowledge and skills in the field of nutrition. Pos Pelayanan Terpadu Lanjut Usia (Posyandu Lansia) is a health facility in the Jomblang village, consisting of the elderly. This study aims to describe the knowledge and incidence of metabolic syndrome in the elderly in the Jomblang village.MethodsThesestudy conducted in the area of Jomblang village, Candisari Village, Semarang City at the beginning until mid-2018. These was a descriptive study with 60 elderly subjects. The data taken were knowledge of metabolic syndrome, body weight, height, waist circumference, blood pressure, blood sugar levels and total cholesterol. Data were taken every month for 3 months.ResultsThe knowledge of the elderly about metabolic syndrome still low. After counseling and intervention, there was an improvement in nutritional status, the incidence of obesity decreased by 3.3%, eldery whose high blood glucose levels increased by 3.3%, elderly whose high cholesterol levels decreased 1.6%. Elderly people who had symptoms of metabolic syndrome are still 6 people (10%), but the elderly who had symptoms of pre-metabolic syndrome decreased to 10 people (17%). Thus, although there were increase in the number of patients with hyperglycemia, in general the symptoms of metabolic syndrome were decreased.ConclusionFurther research is needed to provide real interventions to reduce the incidence of metabolic syndrome in Jomblang village.Keywords: elderly, metabolic syndrom, nutrition knowledge